Laboratory Abnormalities in Pregnancy-associated Hypertension. Issue 3 (September 2015) - Cantu, J.; Clifton, R.G.; Roberts, J.M.; Leveno, K.J.; Myatt, L.; Reddy, U.M.; Varner, M.W.; Wapner, R.J.; Thorp, J.M.; Mercer, B.M.; Peaceman, A.M.; Ramin, S.M.; et al.
<x xml:space="preserve">Abstract</x> (Obstet Gynecol. 2014;124(5):933–940)